A associação da periodontite com a doença pulmonar obstrutiva crônica em modelo experimental e os efeitos do tratamento periodontal associado à terapia fotodinâmica na modulação da inflamação - Rosa, Ellen Perim (2018)
The influence of periodontitis in systemic disease has been much studied, as well as in Chronic Obstructive Pulmonary Disease (COPD). Conventional methods of periodontal treatment (PT) have been associated with adjuvants such as photodynamic therapy (PDT), because it does not present bacterial resistance. Thus, the main of this study was to verify the association between periodontitis and COPD, and PT associated with PDT in the modulation of pulmonary inflammation. The C57Bl/6J mice were randomly divided into eight experimental groups (Basal, Periodontitis (P), P+Treatment (T), P+T+PDT, COPD, COPD+P, COPD+P+T and COPD+P+T+PDT. COPD was induced by orotracheal instillation of 30μl of cigarette extract, 3 times/ week, 7 weeks. Periodontitis was induced by the ligation technique, remaining for 15 days. Periodontal therapy was performed with a curette in the gingival sulcus of the lower first molar. The PDT was performed by insertion of methylene blue (0.005%, 0.05 mg / ml) after irradiation of diode laser with radiant exposure of 318 J / cm2, λ = 660 nm, 9J per point, 2 points, single session. The euthanasia was performed on 51st day, then analyzed the total and differential count of leukocytes in the serum, without femoral lavage and without bronchoalveolar lavage (BAL), histomorphometric analysis of the mandible and lung, serum cytokine levels and in the LBA. The statistical analysis was done by Anova one-way, followed by Student-Newman- Keuls. The COPD+P group presented reduction of IL-6 (p<0.001) and inflammatory infiltrate in LBA (p<0.05), on the other hand, IL-10 was an increase (p <0.001). The association betweem the pathologies may sugest a systemic regulatory mechanism. When the treatment was done with curette and with PDT, IL-6 levels tend to increase in the COPD groups. In conclusion, the conventional treatment of periodontitis and associated PDT is capable of influencing the pulmonary and systemic inflammatory response. Further studies are needed to clarify the regulatory process